ADVOKAT SYARIAH DALAM MEDIASI PERKARA PERCERAIAN MENURUT MAQASHID AL SYARIAH - Hariyanto, Erie; Ni’matunnuriyah, Ni’matunnuriyah (ULUL ALBAB Jurnal Studi Islam, 2017)
The emergence of thinking about the role of profession sharia advocate in the mediation of divorce cases that is derived from a fact produced by the judiciary in solving the case of divorce, which is almost 100% is a conventional decision that essentially have a pattern of win or lose. It is rare to find a win-win solution. Yet the most important is when the judiciary is not only referred to as deciding cases, but also solve the case. One of the alternatives presented in solving the divorce case is based on the win-win solution, The problem to be studied in this article is how the duty and responsibility of sharia advocate profession within the framework of maqahid al syariah. Where the task of sharia lawyers in general is the same as the non-sharia advocate task that is to defend public interest (public defender) and client in upholding justice. But what distinguishes it from non-sharia advocates is in providing defense, counseling, and being authorized for and on behalf of his clients sharia advocates based on the principle of help-help, cling to the source of Islamic teachings. Second, the role of the advocate profession in the mediation of divorce cases should be submitted to a competent advocate, in this case is a sharia advocate. Advocates who have guidelines to always run their profession in accordance with the objectives of syara law (maqashid al syariah).